Calcium-channel blockers decrease clopidogrel-mediated platelet inhibition. Issue 3 (16th August 2009) - Gremmel, Thomas; Steiner, Sabine; Seidinger, Daniela; Koppensteiner, Renate; Panzer, Simon; Kopp, Christoph W
Abstract : Background: The extent of clopidogrel-mediated platelet inhibition varies considerably from one person to the next. Numerous studies have shown that low responders have significantly more adverse events after coronary stenting than patients who respond well to antithrombotic treatment with clopidogrel. Dihydropyridine calcium-channel blockers (CCBs) inhibit the cytochrome P450 3A4 enzyme, which metabolises clopidogrel to its active form. Objective: To investigate the influence of CCBs on clopidogrel-mediated platelet inhibition. Methods: Adenosine-5-diphosphate (ADP)-inducible platelet reactivity was assessed by light transmission aggregometry (LTA) and the VerifyNow P2Y12 assay in 162 patients after percutaneous intervention with stent implantation. Results in the fourth quartiles of both assays were considered as high on-treatment residual ADP-inducible platelet reactivity. Results: Patients with concomitant CCB therapy showed a significantly higher on-treatment platelet reactivity than patients without CCB medication (p=0.001 for both assays). Further, high on-treatment residual ADP-inducible platelet reactivity was significantly more common among patients currently taking CCBs (p=0.001 for LTA and p=0.004 for the VerifyNow P2Y12 assay). A multivariate regression analysis confirmed CCB therapy as an independent predictor of reduced clopidogrel-mediated platelet inhibition (p=0.006 for LTA and p=0.004 for the VerifyNow P2Y12 assay). Conclusion: CCBs decrease clopidogrel-mediated platelet inhibition in patients undergoing angioplasty and stenting for cardiovascular disease.